Hubungan antara Core Beliefs, Rumination, Dukungan Sosial, dan Post Traumatic Growth pada Anak Usia Sekolah - M. Ramadhana; H. S. Shinto S. (Jurnal Ilmiah Psikologi MIND SET, 2017)
Post-traumatic growth is one of those terms for positive change experienced as a result of the struggle with trauma which emphasize in transformation (Meyer, Grant, and Kilmer, 2011). Tedeschi and Calhoun (2004) also emphasize seismic event which caused psychological crisis because of the disruption of core beliefs so that post-traumatic growth could happen. The following research is to identified post-traumatic growth that happen in school-age children with horrible experience. Results showed that there is post-traumatic growth in school-age children with horrible experience. Increased core beliefs, rumination, and social support strengthen post-traumatic growth in school-age children with horrible experience.